Latin American Countries Stuck in the Field of Development Theory: A Case Study of Chile - Yang, Jiaqi (International Journal of Social Sciences and Public Administration, 2024)
This manuscript conducts a nuanced exploration of the ramifications associated with the adoption of neoliberal development theories in Latin America, with a particular emphasis on the Chilean experience. It delves into the comprehensive implementation of neoliberal reforms under the auspices of the Washington Consensus during the 1970s, charting the trajectory of Chile's economic hardships, its subsequent period of growth, and the enduring challenges of socio-economic inequality and insufficient social welfare systems. Despite Chile's transformation into one of the region's most affluent countries, the analysis exposes the intricate relationship between economic advancements and the overarching well-being of society. The widespread protests in 2019 against entrenched neoliberal policies serve as a poignant critique of the tangible disconnect between macroeconomic success and the populace's quality of life. Through this case study, the paper advocates for a recalibration of development theories to equally value human rights and social progress as indispensable counterparts to economic prosperity, proposing a more integrated framework for sustainable development.